Positive Gender Responses to Hate Speech of ‘The Little Mermaid’ on Twitter: Critical Discourse Analysis - Lailiah, Alfia Rismatul (Language Horizon: Journal of Language Studies, 2023)
Hate speech indicates hatred, prejudice, or discrimination toward individuals or groups due to appearance, race, religion, etc. Hate speech quickly occurs on social media; everyone can be the victim, like Disney posted about Little Mermaid on Twitter. People filling the comment section of Disney posted with the reactions, including hate speech and positive responses toward Halle as the character of Ariel. This study aims to find the different positive responses of women and men toward hate speech using women’s and men’s language features, stereotyped language that appears in a positive response, present the category of hate speech, and why people spread hate in The Little Mermaid post. The research uses the Critical Discourse Analysis approach by Van Dijk (1995) and Fowler (1991). The data were analyzed using the qualitative research method and presented with descriptive text. The data object is taken from the two Tweets Disney posted about The Little Mermaid on Twitter. The result proved that there is a different way when women and men respond positively to hate speech through women’s and men’s features but the positive responses of females are more polite than males. Although in positive responses, this study showed that stereotyped language of perceived category essentialism appeared, focused on the term of race. This study presented only seven categories of hate speech that occurred and why people spread hate to convey their disappointment with Disney’s decision that the main actress did not meet the expectation like in animation.